Chronic lymphocytic leukemia (CLL) treatment: So many choices, such great options. Issue 9 (26th February 2019) - Sharma, Sandhya; Rai, Kanti R.
Abstract : Within a period of just over a decade, managing chronic lymphocytic leukemia (CLL) has become more effective and yet more challenging than ever before. The important improvement in the treatment of CLL can be ascribed to the availability of many new options, mainly with the development of novel targeted therapies, such as ibrutinib, idelalisib, duvelisib and venetoclax. There are now newer tests that reliably define high‐risk patients, and treatment plans can be tailored accordingly. Overall, this indeed is a new era in the treatment of patients with CLL. However, despite this progress, CLL remains an incurable disease and continues to remain challenging. In this brief review, the authors highlight the many great choices available to clinicians who manage patients with CLL and focus on the sequencing of these choices based on the available data. Abstract : Within a period of just over a decade, managing chronic lymphocytic leukemia has become more effective and yet more challenging than ever before. However, despite this progress, chronic lymphocytic leukemia remains an incurable disease without allogeneic stem cell transplantation and thus remains a challenge.